Lexical Right-sizing in the Evolution of Spanish: Understanding Language as a Complex Adaptive System. Issue 7 (July 2016) - Elerick, Charles
Abstract : Researchers of Latin and its evolution to Spanish have observed that short forms tend to be replaced by more robust forms ( ōs by bucca (> Sp. boca )). This observation represents a starting point for the systematic study of the effect of loss of phonological bulk, compensation mechanisms, and the operation of this phenomenon in Latin > Spanish evolution. The mechanisms of compensation for the loss of phonological bulk are phonological adjustments, morphological augment, and lexical replacement. Forms that are underweight, so to speak, occasion an increase in bulk, while new constructions, as they are reduced to lexical forms, lose phonological material quickly ( tenēre habeō > tendré ). This reflects the Theory of Communication of Shannon and Weaver (1949). Zipf (1965) showed that the length of words is inversely related to frequency and that word length shows a direct relationship to semantic complexity. The evolution of the Spanish lexicon expresses the principles captured in their formulations. The process of change that maintains the phonological– semantic macro-stability reflects the functioning of language as a Complex Adaptive System. Users of a language propose and accept (or reject) innovations that tend to optimize communication and these propagate, creating a vast diachronic network of diffusion. This self-regulating mechanism of language change maintains balance in the lexicon.